Internalizing PO-5 (Pomaemaeka) Values to Prevent Educational Transgressions: Focus on Sexual Violence - Hartinawanti Hartinawanti; Nurhayati Nurhayati (ELS Journal on Interdisciplinary Studies in Humanities, 2025)
This study aims to determine and analyze the internalization of “PO-5 (Pomaemaeka)” values in education and as efforts to prevent 3 major sins in education in Indonesia, especially sexual violence for students in Wolio District. This study was analyzed using qualitative and quantitative approaches. The population of this study were all students in Wolio District. The sampling technique used simple random sampling so that a sample of students from junior to senior high school level was determined which represented a population of 42 people. Data collection techniques through observation, questionnaires and interviews. The data analysis technique used quantitative data techniques, namely descriptive statistical tests and inferential statistics, while qualitative data techniques were data reduction, data display and data verification. The results showed that the internalization of “PO-5” values in education for students in Wolio District was in the 'Often' category with a score interval of 46-59 as many as 18 respondents, a percentage of 42.86%; One of the efforts to prevent 3 major sins in education, especially sexual violence for students, is to internalize “PO-5” values in education comprehensively at all levels of education.